Water security - Sadoff, Claudia W.; Grey, D.; Borgomeo, Edoardo (Oxford University Press, 2020)
Water security has emerged in the 21st century as a powerful construct to frame the water objectives and goals of human society and to support and guide local to global water policy and management. Water security can be described as the fundamental societal goal of water policy and management. This article reviews the concept of water security, explaining the differences between water security and other approaches used to conceptualize the water-related challenges facing society and ecosystems and describing some of the actions needed to achieve water security. Achieving water security requires addressing two fundamental challenges at all scales: enhancing water’s productive contributions to human and ecosystems’ well-being, livelihoods and development, and minimizing water’s destructive impacts on societies, economies, and ecosystems resulting, for example, from too much (flood), too little (drought) or poor quality (polluted) water.